Credit Growth, Risk, and Liquidity Signals: Effects on ROA and Stock Returns in Indonesian Banks (2020–2024), Moderated by Inflation - Joshua Ringgas Matondang; Mochammad Ridwan Ristyawan; Ramadania; Wendy; Anggraini Syahputri (Politeknik Ganesha Medan, 2026)
This study examines credit growth, Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Loan-to-Deposit Ratio (LDR) impact on Return on Assets (ROA), and ROA's influence on stock returns, with inflation as moderating variable in Indonesian conventional banks from 2020-2024. Using purposive sampling, 39 banks from the Indonesia Stock Exchange yielded 166 unbalanced panel observations analyzed through Fixed and Random Effect Models in EViews 12. Results show varying statistical support. At 5% significance, credit growth positively drives ROA while NPL negatively affects it, confirming asset quality and lending volume as profitability determinants. LDR shows a strong negative influence on stock returns, establishing liquidity ratio as the primary market signal, while CAR shows no significant effect on ROA. At 10% significance, inflation exhibits a weak negative moderating effect on the ROA-stock return relationship, providing marginal statistical evidence. ROA does not significantly impact yearly annual stock returns nor mediate relationships between independent variables and returns. This suggests liquidity metrics may carry greater weight than profitability signals, though constrained by the model's limited explanatory power. Findings indicate bank managers should prioritize NPL control and maintain optimal LDR thresholds to preserve profitability and investor confidence, while emphasizing risk metrics in communications. Regulators should strengthen liquidity oversight through enhanced LDR disclosure requirements. Limitations include post-pandemic focus and limited variables. Future research should examine NPL threshold effects, incorporate macroeconomic and operational efficiency measures, and compare cross-country data between crisis and stable periods.